Representações sociais de feminismo em contextos de ruralidade : um estudo com mulheres rurais no sertão da Bahia - Míria Moraes Dantas (2022)
Feminism does not emerge with a fixed date, but embodied in women's history. It constitutes a social phenomenon whose meaning path beyond its lexical circulation and is crossed by the practice-movement-epistemology triad. Women, as they are the main figures in the foundation and development of this phenomenon, contribute to the orientation of its meaning, as well as its plural and multifaceted features. In the sphere of ruralities, the plural understanding of feminism provides an opportunity for studies that consider rural women as part of the construction of knowledge. Articulation perceived by the literature as scarce, particularly, in the field of psychology, in which both rural women and ruralities still appear doubly invisible or associated from generalist and urban-centered perspectives. In this sense, when we take feminism as an object of social representation for rural women, we are interested in understanding how collectively shared meanings about this object are manifested through the speeches and daily practices of these women, considering them from the multidimensionality of their life contexts. Therefore, the Social Representations Theory is used in order to identify and comprehend how, and whether, social representations of feminism are constructed for women in rural contexts located in Monte Santo, in the interior of Bahia, northeast of Brazil. This was an exploratory research whose data collection strategies were aligned with the care required by health agencies, regarding the risks of contamination by the new coronavirus (Sars-coV-2), as well as the impact of this crossing in the research in ruralities. We used as a research instrument a semi-structured survey form (digital and printed) composed of open and closed questions and the Technique of Free Association of Words (TALP). Sixty-two women, from different age groups, educated and not educated, participated in the collection period. The data were subjected to simple frequency analysis and content analysis. The results revealed the existence of a representational field of feminism still under construction, whose elaboration is represented by specificities related to the modes of subjectivation, inscription/social interaction networks, communicative contexts and the generational marker of the interviewees. It was noted that the social representations of feminism for young women are constituted from the accessibility to a historical and political memory, to collective claims and social demands guided by the nominated feminism. Constituting itself for adult women from that unsaid, from a personal complaint that denounces a place crossed by gender expectations, violence, and femicide. And that, although most still do not act in feminism in a named sense, they can understand its guidelines and objectify them by way of daily practice. Ultimately, the results denounce the invisibility and silencing in which the Brazilian rural women are even exposed, provoking us to continue investing in research that contributes to the disarticulation of this social problem.